2015
DOI: 10.1515/bvip-2015-0030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the proliferative activity of immunocompetent cells in the jejunal and iliac lymph nodes of prepubertal female wild boars diagnosed with mixed mycotoxicosis

Abstract: The study evaluated the proliferative activity of immunocompetent cells in the jejunal and iliac lymph nodes of prepubertal female wild boars exposed to deoxynivalenol and zearalenone in naturally contaminated feed. The evaluation was performed with the use of the MTT assay and 2 mitogens: lipopolysaccharide (LPS) and concanavalin A. Intensified proliferative processes in T and B lymphocytes were revealed. The mitogenic activity of LPS was more expressed in the lymphocytes of both iliac and jejunal lymph nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…The first is the body’s failure to recognise the threat [24], which is consistent with the T-regs theory [25]. The second is the compensatory effect, namely increased absorption to compensate for the physiological deficiency of endogenous steroids [26,27].…”
Section: Introductionmentioning
confidence: 73%
“…The first is the body’s failure to recognise the threat [24], which is consistent with the T-regs theory [25]. The second is the compensatory effect, namely increased absorption to compensate for the physiological deficiency of endogenous steroids [26,27].…”
Section: Introductionmentioning
confidence: 73%
“…Recent investigations showed that DON affects the composition of the basement membrane proteins and influences the migration of lymphocytes into the mucosal epithelium [ 53 ]. Zielonka et al [ 54 ] revealed an increase in the proliferative activity of immunocompetent cells harvested from the jejunal and ileal lymph nodes of pre-pubertal, female wild boars exposed to DON (1008 μg/kg of feed) and ZEN (26 μg/kg of feed) for seven days in naturally contaminated feed. Therefore, it can be assumed that long-term (six-week) exposure to low and combined doses of ZEN and DON in feed intensifies lymphocyte proliferation in the mesenteric lymph nodes of the jejunum.…”
Section: Resultsmentioning
confidence: 99%
“…Doses below the lowest observed adverse effect level (LOAEL) values [ 8 , 9 ] that produce subclinical symptoms of disease are referred to as no observed adverse effect levels (NOAEL) doses [ 10 ]. The lowest measurable dose that enters positive interactions with the host’s body in various stages of life is known as the minimal anticipated biological effect level (MABEL) dose [ 11 ]. The dose-response paradigm has been undermined by the low dose hypothesis.…”
Section: Introductionmentioning
confidence: 99%